Analisis Korelasi untuk Mengetahui Keeratan Hubungan antara Keaktifan Mahasiswa dengan Hasil Belajar Akhir - Cindy Cahyaning Astuti (Universitas Muhammadiyah Sidoarjo, 2017)
Teaching and learning can be defined as a process that contains a series of actions between educators and learners on the basis of reciprocal relationships that take place in an educational situation in order to achieve certain goals. Interaction or reciprocal relationship between educators and learners is a key condition for the continuity of the learning process. The process of interaction can be said to work well if the students can actively participate in the learning process. Active participation by students is expected in the learning process to determine the level of understanding of the material presented. The purpose of this research was to determine the relationship between the activity of students to learn the final results were analyzed using correlation analysis. The case studies in this research were students PTIK half of 1 course of Calculus Elementary School Year 2015/2016. Based on the analysis of correlation obtained by the correlation coefficient of 0.857 which indicates that there is a high positive correlation between the activity of the student (X) and the value of the final learning outcomes (Y). Besides the correlation coefficient of 0.857 can also mean that increasing the value of the activity of the student (X) then the value of the final learning outcomes (Y) will also increase. For the hypothesis testing results of the correlation coefficient can be concluded that with a confidence level of 95% is sufficient evidence to suggest that there is a statistically significant relationship between the activity of the student (X) and the final learning outcomes (Y).